Quality aspects relating to giving birth in Switzerland: An analysis of quality indicators in inpatient obstetrics from 2013 to 2017 - Dominik Moser; Dominik Moser; Dominik Moser; Dominik Moser (Frontiers Media S.A., 2022)
Quality transparency supports the reduction of information asymmetries in the health care system and enables the targeted regulation of health care. This study examines quality variation in inpatient obstetric care using the official Federal Office of Public Health Inpatient Quality Indicators (CH-IQI; vaginal births with 3rd- and 4th-degree perineal tears, vaginal births with episiotomy, and Caesarean section for low-risk births). It includes 101 maternity hospitals and 425,810 births between 2013 and 2017. For births with perineal laceration of 3rd and 4th degree, Switzerland performs 0.9% poorer in comparison to Germany (D-IQI) and Austria (A-IQI). For births with episiotomy, Switzerland is 1.1% above Germany. The Caesarean section rate for low-risk births was 26.8% in Switzerland in 2017 (Germany: 25.9%). When comparing Swiss clinics, private clinic locations in particular stand out. One possible reason for this may be the density of care, patient demands or the system of affiliated physicians at these clinics.